2009
DOI: 10.1245/s10434-009-0863-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement the Prediction of Postoperative Survival in Gastric Cancer by Combining the Negative Lymph Node Count with Ratio Between Positive and Examined Lymph Nodes

Abstract: The NLN count is a key factor for improvement of survival prediction of RML in gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 32 publications
7
56
2
Order By: Relevance
“…The 5-year overall survival (OS) rate was determined by Kaplan-Meier, and statistical differences between groups were calculated with the log-rank test. We adopted the cut-point survival analysis to determine the most appropriate cutoffs for NLN and LNR (10,11,15). According to log rank test χ 2 statistics, we compared the ability to differentiate among subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-year overall survival (OS) rate was determined by Kaplan-Meier, and statistical differences between groups were calculated with the log-rank test. We adopted the cut-point survival analysis to determine the most appropriate cutoffs for NLN and LNR (10,11,15). According to log rank test χ 2 statistics, we compared the ability to differentiate among subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…It's necessary to bring NLN count into the system of prognosis prediction in breast cancer. Many researchers have suggested that NLN count is closely related to the prognosis in gastric cancer (11), colon cancer (12), esophageal cancer (13), and cervical cancer (14). However, few data has been published to elucidate the importance of NLN count in breast cancer prognosis.…”
Section: Original Articlementioning
confidence: 99%
“…A cut-point analysis was performed to determine the cutoffs of the pTV value that determine the greatest actuarial survival difference among the resulting subgroups. 15 Results demonstrates that the appropriate cutoffs of pTV for verification the statistically significantly survival differences between resulting subgroups were 4.0, 10.0, 20.0, and 36.0 ( Table 1). The KaplaneMeier method analyzed OS rates according to the new subgroup of pTV, and the results showed that there were significant survival differences among 14 patients with pTV1 (0.50 Tumor volume 4.00), 33 patients with pTV2 (4.…”
Section: Patientsmentioning
confidence: 94%
“…[5][6][7][8] We previously demonstrated that the number of negative nodes could enhance the accuracy of predicting the prognosis of patients for both the N stage and the R PD . 9,10 Recently, we demonstrated that the ratio between negative and positive lymph nodes (R NP ) is associated with prognosis prediction for smallscale patients with positive lymph node metastasis. 11 To test the clinical applicability of R NP for prognostic prediction in GC, we designed this study to elucidate the most accurate prognostic predictor among N stage, R PD , and R NP for large-scale GC patients.…”
mentioning
confidence: 99%